PLANNING AND ORGANIZING LAND USE OF TERRITORIAL COMMUNITIES (CASE OF KOMARNO TERRITORIAL COMMUNITY) - Dudych Г. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The features of spatial planning for territories are discussed as a complex process aimed at the efficient use of land resources, ensuring environmental sustainability, and promoting sustainable development within communities. The author analyzes the legislative aspects of land use planning, particularly focusing on the requirements outlined in the Law of Ukraine titled “On Amendments to Certain Legislative Acts of Ukraine on Land Use Planning.” This law mandates the creation of a comprehensive plan for the spatial development of community territories. The natural resource potential of the Komarno territorial community in Lviv region is examined, along with an assessment of its land resources, level of development, and environmental sustainability. It has been established that a significant portion of the community, specifically 74.2%, is classified as agricultural land, with 42.5% of this land being plowed. Additionally, forestry land accounts for 15.1% of the total area. The main environmental issues facing the community include river channel siltation, flooding, and outdated reclamation systems that require reconstruction. The coefficient of ecological sustainability for the territory (Kec.s = 0.46) indicates an unstable ecological state, while the coefficient of anthropogenic load (Ka.l = 3.4) reflects a moderate level of impact from economic activities. The author proposes a series of measures to enhance the effectiveness of spatial planning within the community, including: conducting an inventory and certification of land resources; improving the engineering layout of the territory, specifically by reconstructing land reclamation systems; updating the master plans for settlements; creating opportunities to attract investors through the auction sale of commercial land plots; and increasing the area of natural lands to bolster the environmental sustainability of the community. Furthermore, the author advocates for a transition to innovative land use models and the adoption of an agro-landscape approach to land management. It is emphasized that developing a comprehensive plan for spatial development will foster economic growth, enhance investment attractiveness, and contribute to the environmental sustainability of the community.